Analysis of the Influence of Perceived Ease of Use, Service Content Quality, Customer Service Quality on Continuance Intention Through Customers Satisfaction in Users My Telkomsel in Manado - Yolanda Soedibyo; Gerald Stevanus Sumual Sompie (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
MyTelkomsel application is a self-service formed by Telkomsel as an application that can help users manage accounts and access customer services via smartphones. MyTelkomsel is an application that provides information on users in a provider. This study aims to determine the effect of Perceived Ease of Use, Service Content Quality, Customer Service Quality on Continuance Intention through Customer Satisfaction. The expected benefits of this research are that it can contribute to the development of science specifically on factors that can affect Continuance Intention based on the influence variables of Perceived Ease of Use, Service Content Quality, Customer Service Quality, and Customer Satisfaction. This research is a causal research that uses a quantitative approach and uses AMOS 24.0 software as data processing to process primary data from 125 MyTelkomsel application users in Manado who have been collected using the Snowball Sampling technique. The characteristics of the respondents in this study are male and female, aged 18-60 years, domiciled in Manado, downloaded MyTelkomsel application independently, used MyTelkomsel application at least once in 12 months, actively using MyTelkomsel application until now, and have contacted Vero in MyTelkomsel application. The results of this study are that all variables in the study have a positive and significant effect on Continuance Intention, namely, Perceived Ease of Use, Service Content Quality, Customer Service Quality.